Well-being needs of Master of Business Administration (MBA) students at the University of Free State - Sinra, Ronald Wesley (University of the Free State, 2024)
Well-being among postgraduate students is increasingly recognised as crucial for academic success and personal development. Yet, many experienced high levels of stress, anxiety, and isolation, impacting their overall academic experience. This qualitative research study explores the well-being of Master of Business Administration (MBA) students at the University of Free State, aiming to identify the well-being needs and support required, in addition to the services provided by the institution. The study adopted a qualitative research approach and interpretive phenomenological design. A population of 131 MBA students who were enrolled were approached to participate voluntarily. From the initial voluntary sample group of 25 MBA students, 14 semi-structured interviews were conducted, and reflexive thematic analysis was appointed to answer the main research question. The thematic analysis led to the identification of five themes and a variety of subthemes coupled with them: 𝗦𝘂𝗽𝗽𝗼𝗿𝘁, 𝗘𝘅𝗽𝗲𝗿𝗶𝗲𝗻𝗰𝗲 𝗼𝗳 𝗪𝗲𝗹𝗹-𝗕𝗲𝗶𝗻𝗴, 𝗡𝗲𝗲𝗱𝘀, 𝗗𝗲𝗺𝗮𝗻𝗱𝘀 𝗮𝗻𝗱 𝗥𝗲𝘀𝗼𝘂𝗿𝗰𝗲𝘀. 𝗦𝘂𝗽𝗽𝗼𝗿𝘁: Students highlighted the significance of both emotional and institutional support systems. Positive relationships with faculty and fellow students cultivated a sense of belonging and enhanced their resilience. 𝗘𝘅𝗽𝗲𝗿𝗶𝗲𝗻𝗰𝗲 𝗼𝗳 𝗪𝗲𝗹𝗹-𝗕𝗲𝗶𝗻𝗴 is where participants reported a complex interplay of emotional, social, and academic well-being, emphasising the importance of a balanced lifestyle to maintain mental health during their studies. 𝗡𝗲𝗲𝗱𝘀 indicated in the findings revealed specific needs related to academic guidance, mental well-being resources, and work-life balance, emphasising the necessity for tailored support services. 𝗗𝗲𝗺𝗮𝗻𝗱𝘀 that refer to the demands of the MBA program, including intensive coursework and time pressures, were identified as significant stressors, contributing to feelings of being overwhelmed and burnout. 𝗥𝗲𝘀𝗼𝘂𝗿𝗰𝗲𝘀 relate to the students’ expression of the need for better access to resources, including communication, collaboration and peer learning, information technology, counselling services, and stress management workshops, to help them navigate their academic challenges effectively. The findings emphasise the critical role of institutions in supporting student well-being, suggesting that a structured approach that addresses these themes can significantly enhance the overall academic experience of MBA students. This result contributes to the growing body of literature on student well-being in higher education. It offers practical to implement effective support systems for MBA students. Various recommendations to support the well-being needs of MBA students better were identified in this study. These speak to the 𝘪𝘯𝘤𝘭𝘶𝘴𝘪𝘰𝘯 𝘰𝘧 𝘸𝘦𝘭𝘭-𝘣𝘦𝘪𝘯𝘨 𝘵𝘰𝘱𝘪𝘤𝘴 𝘪𝘯 𝘵𝘩𝘦 𝘔𝘉𝘈 𝘤𝘶𝘳𝘳𝘪𝘤𝘶𝘭𝘶𝘮, 𝘵𝘩𝘦 𝘤𝘰𝘯𝘥𝘶𝘤𝘵 𝘰𝘧 𝘳𝘦𝘨𝘶𝘭𝘢𝘳 𝘸𝘦𝘭𝘭-𝘣𝘦𝘪𝘯𝘨 𝘸𝘰𝘳𝘬𝘴𝘩𝘰𝘱𝘴, 𝘪𝘯𝘷𝘰𝘭𝘷𝘦𝘮𝘦𝘯𝘵 𝘰𝘧 𝘱𝘦𝘦𝘳 𝘴𝘶𝘱𝘱𝘰𝘳𝘵 𝘱𝘳𝘰𝘨𝘳𝘢𝘮𝘮𝘦𝘴, 𝘱𝘦𝘳𝘴𝘰𝘯𝘢𝘭𝘪𝘴𝘦𝘥 𝘢𝘤𝘤𝘦𝘴𝘴 𝘵𝘰 𝘤𝘰𝘶𝘯𝘴𝘦𝘭𝘭𝘪𝘯𝘨 𝘴𝘦𝘳𝘷𝘪𝘤𝘦𝘴, 𝘪𝘯𝘤𝘰𝘳𝘱𝘰𝘳𝘢𝘵𝘪𝘰𝘯 𝘰𝘧 𝘧𝘢𝘤𝘶𝘭𝘵𝘺 𝘮𝘦𝘮𝘣𝘦𝘳𝘴 𝘪𝘯 𝘤𝘰𝘰𝘳𝘥𝘪𝘯𝘢𝘵𝘪𝘰𝘯 𝘰𝘧 𝘴𝘦𝘳𝘷𝘪𝘤𝘦𝘴 𝘢𝘯𝘥 𝘭𝘢𝘴𝘵𝘭𝘺, 𝘱𝘳𝘰𝘮𝘰𝘵𝘪𝘰𝘯 𝘰𝘧 𝘸𝘰𝘳𝘬-𝘭𝘪𝘧𝘦 𝘣𝘢𝘭𝘢𝘯𝘤𝘦 approaches. Ultimately, gradual implementation of the recommended initiatives will eventually enhance the overall well-being of MBA students.
Dissertation(MBA (Business Administration))--University of the Free State, 2024
Keywords: MBA; Interpretive phenomenological analysis; Thematic analysis; Support; Experience of well-being; Needs; Demands; Resources